FERGHANA VALLEY: ROBLEMS OF MAINTAINING ECONOMIC STABILITY - DANKOV, Artem (CENTRAL ASIA AND THE CAUCASUS, 2007)
The Central Asia region, which is located in the very heart of the vast Eurasian continent at the crossroads where four of the largest civilizations (Russian, Chinese, Indian, and Islamic) meet, has a long and profuse history teeming with difficulties and conflicts.The Ferghana Valley is a territory where all the problems of the Central Asia region (border conflicts, poverty, shortage of fertile land and water resources, unemployment, ethnic disputes, and so on) are concentrated and come together in a tangled ball of contradictions. So an analysis of the main, primarily economic, problems of the Ferghana Valley is vital to understanding the overall situation in Central Asia and around it.The Ferghana Valley, an intermontane depression nestled in the foothills of Tien Shan, up to 300 km in length from the West to the East and up to 170 km from north to south, is one of the main agricultural regions of Central Asia. Only four roads (Ferghana-Tashkent, Ferghana-Khujand, OshBishkek, and Osh-Khorog) and one railroad branch (Ferghana-Khujand) link the valley to the outside world.In Soviet times, national-state demarcation was carried out in Central Asia, including in the Ferghana Valley, on the basis of a rather arbitrary idea of ethnic borders. The Ferghana Valley, which was always a single area, was divided by the administrative borders of Uzbekistan, Kyrgyzstan, and Tajikistan, which acquired the status of state borders after the collapse of the U.S.S.R. Today, this change in status is giving rise to many problems. The borders divide a previously indivisible region and have broken down historical economic, cultural, and political ties. The flat part of the valley belongs to the Republic of Uzbekistan and is divided into the Andijan, Namangan, and Ferghana regions. The eastern part of the valley as well as the mountains and foothills surrounding the valley from the north, east, and south belong to the Republic of Kyrgyzstan and are part of the Osh, Jalal-Abad, and Batken regions. The western part of the valley belongs to the Sogd (former Leninabad) Region of the Republic of Tajikistan.